Tensions in Designing a Third Space in a Justice-Oriented Teacher Residency: Toward an Authentic Collaborative for Clinical Practice. Issue 1 (1st January 2021) - Hackett, Jacob; Williams, Rhina; Davis, Camea; Cross, Stephanie Behm; Behizadeh, Nadia; Hearn, Elizabeth
ABSTRACT: Urban teacher residencies and university-district partnerships are growing in popularity in the United States and are vital for the clinical practice of preservice teachers. Because urban residencies and university-district partnerships are situated in historically marginalized communities, they strive to prepare teachers with a mind and skill set oriented toward social justice. The Georgia State CREATE Residency strives to prepare critically conscious and skilled educators for Atlanta. Here, we analyze how stakeholders representing the university, residency administrative team, and K–12 partner school and district leaders collaborated to learn from and design a responsive teacher residency. By comparing findings to AACTE's recently published 10 essential proclamations of high-quality clinical practice, we argue that administrative learning spaces must exist to surface cultural and historical understanding of where residencies and partnerships are located in order to work toward transformative teacher preparation and induction. A critical analysis of the tensions and contradictions within a teacher residency can aid stakeholders in authentically crossing traditional teacher-education boundaries. Implications for further research are provided.